Self-narrating cloth: The aesthetics of (a) weaving - Priemus, Jessica (Charles Sturt University, 2020)
Despite almost universal participation in textile use, understanding of the fundamentals of textile construction within the global north appears to be increasingly superficial. The typical person is largely unexposed to the making process of textiles and textile products, as production is outsourced to locations distant from the final user. In recent years, fashion and textile designers have attempted to engage users in their making processes through the use of various supporting media. My intention is not to disregard the production of additional media, but to propose a turn to utilising the textile itself as the site for further user engagement. In this article, I reflect on my experiences working with weavers in rural Bangladesh as part of my creative practice and postgraduate research. There, through multisensorial observation, I began to see each 'weaving' (noun/verb) not as a flat thing but as a multidimensional changescape (Gibson vii). Ephemeral moments occurring during the making process were found to materialise within each weaving, acting as a physical record of the spatial, temporal and personal traces of making. Using photography, these traces have been visually amplified in order to involve each weaving in the narration of its own creation.